2008
DOI: 10.1158/1078-0432.ccr-07-5252
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Metabolic Heterogeneity of Cervical Cancer

Abstract: Purpose: Previous research has shown that the intertumoral maximum standardized uptake value (SUV Max ) of F-18 fluorodeoxyglucose (FDG)^positron emission tomography (PET) for cervical cancer predicts disease outcome. The purpose of this study was to evaluate the pretreatment intratumoral metabolic heterogeneity of FDG. Experimental Design: This is a prospective cohort study of 72 patients with International Federation of Gynecology and Obstetrics stages Ib1 to IVa cervical cancer treated with chemoradiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 45 publications
4
89
2
Order By: Relevance
“…The intratumoral metabolic heterogeneity was represented by the heterogeneity factor (HF) [16], which was determined for each patient as follows: a region of interest (ROI) was manually drawn to fully include the primary tumor and a surrounding region of normal tissue (normal background). The tumor volume was determined with a series of SUV thresholds (e.g., 40%, 50%, 60%, 70%, and 80% of SUVmax) using the semiautomatic software of the workstation (Advantage Workstation 4.3, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…The intratumoral metabolic heterogeneity was represented by the heterogeneity factor (HF) [16], which was determined for each patient as follows: a region of interest (ROI) was manually drawn to fully include the primary tumor and a surrounding region of normal tissue (normal background). The tumor volume was determined with a series of SUV thresholds (e.g., 40%, 50%, 60%, 70%, and 80% of SUVmax) using the semiautomatic software of the workstation (Advantage Workstation 4.3, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, in two studies in cervical cancer a metric based on a “volume versus threshold curve” was not able to predict outcome in 73 patients [67], contradicting a previous assessment in the same cohort [70]. Although other first-order features such as standard deviation, skewness and kurtosis were also included, it should be emphasized that this study essentially highlighted the fact that the metric based on the “volume versus threshold curve” is a surrogate for volume, not a measurement of heterogeneity (see also Supplementary material).…”
Section: Statistical Issuesmentioning
confidence: 99%
“…In cervical cancer, the inter-tumoral maximum value of FDG uptake (SUV Max ) has been shown to be predictive of outcome. However, more recent studies have shown that SUV heterogeneity was more predictive of lymph node metastasis at diagnosis and radiation response and progression-free survival (34). In this study, volumes were derived using adaptive image segmentation and using the pretreatment FDG-PET/CT images.…”
Section: Functional and Metabolic Imaging Of Tumor Heterogeneity: Dcementioning
confidence: 99%